Does Ménière's Disease in the Elderly Present Some Peculiar Features?. (25th October 2012) - Teggi, R.; Meli, A.; Trimarchi, M.; LiraLuce, F.; Bussi, M.
Abstract : Object . Aim of our study was to establish some peculiar features of Ménière's Disease (MD) in a group of elderly MD patients, in which the first vertigo spell happened when over 65 years old. Material and Methods . We analyzed a group of 73 younger than 65-years-old and a group of 30 elderly MD patients. All patients underwent a neurotological evaluation, an anamnestic evaluation including a lifetime history of migraine, and blood withdrawal for autoantibody screening. Results . Some differences were found between elderly and younger MD patients. Elderly MD patients presented a higher prevalence of Tumarkin attacks and a lower prevalence of lifetime history of migraine; moreover, they presented a faster develop of hearing loss and vertigo spells than a subgroup of 32 younger patients matched for the duration of illness. Conclusions . Some clinical features of MD in elderly have been pointed out. Particularly, the lower rate of migrainous history and positivity for autoantibodies often associated with MD, in our opinion, support the hypothesis of a vascular disorder acting as a predisposing factor for MD in elderly.